Perancangan Sistem Informasi Akuntansi Penjualan Tunai Pada UMKM Dedi Tani - Yulsiati, Henny; Sonia, Sonia (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2025)
This final report is entitled "Design of Cash Sales Accounting Information System at UMKM Dedi Tani". UMKM Dedi Tani is a type of business that operates in the field of fertilizer and pesticide trading. This report aims to design and implement a computerized cash sales accounting information system based on Microsoft Access at UMKM Dedi Tani, in order to make it easier for UMKM to find out the amount of revenue based on the type of product and the amount of cash received from these cash sales. The author collects primary data obtained from interviews with employees regarding the sales accounting system that has been implemented at this time. The Dedi Tani UMKM cash accounting information system has several weaknesses such as manual recording which is no longer effective as many buyers, difficulty in making sales recaps, difficulty knowing exactly which types of goods have increased sales and provide high profits and which goods have decreased and provide low profits. Finally, the author concludes that the design of the Dedi Tani UMKM cash sales accounting information system application goes through the stages of analyzing the old system with designing a new computerized system, designing applications, and testing application results that have outputs in the form of a new system.Keywords: Accounting Information System, and Microsoft Access